2014
DOI: 10.1002/cncy.21455
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a suspicious afirma test result in thyroid fine‐needle aspiration cytology: An institutional experience

Abstract: BACKGROUND: Fine-needle aspiration (FNA) biopsy is the most frequently used method for thyroid nodule evaluation.However, up to 30% of cases are considered indeterminate. Surgery is typically recommended for these cases, but up to two-thirds of indeterminate cases are found to be benign. The Afirma test is used for the preoperative classification of thyroid nodules with indeterminate cytology. This study reviews the authors' institutional experience with Afirma. METHODS:A cohort of 132 cases of thyroid FNA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 17 publications
13
125
1
Order By: Relevance
“…Thus, more classical type PTCs are present in the SUS category than in the AUS/FLUS or SFN categories (19)(20)(21)(22)(23). Our findings are consistent with those reported by Lastra et al who found that of the malignant tumors resected at their institution with a suspicious Afirma result and a preceding AUS/FLUS or SFN diagnosis, 73% were FVPTCs (the FVPTCs were not further subclassified in this study), 14% were classical PTCs, and 14% were FTCs (24). Moreover, the finding that many of the carcinomas detected by the GEC are NFVPTCs is a direct reflection of the fact that the Bethesda categorization of a nodule is associated with tumor type, stage, and prognosis (22,25).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, more classical type PTCs are present in the SUS category than in the AUS/FLUS or SFN categories (19)(20)(21)(22)(23). Our findings are consistent with those reported by Lastra et al who found that of the malignant tumors resected at their institution with a suspicious Afirma result and a preceding AUS/FLUS or SFN diagnosis, 73% were FVPTCs (the FVPTCs were not further subclassified in this study), 14% were classical PTCs, and 14% were FTCs (24). Moreover, the finding that many of the carcinomas detected by the GEC are NFVPTCs is a direct reflection of the fact that the Bethesda categorization of a nodule is associated with tumor type, stage, and prognosis (22,25).…”
Section: Discussionsupporting
confidence: 92%
“…There is a tendency for the Afirma GEC test to report a high percentage of benign Hürthle cell nodules as suspicious. 13,15,16,18,19 These studies indicate that the risk of malignancy for a suspicious Afirma result is lower for aspirates with Hürthle cell cytology (19%-23%) than for those without a prominent population of Hürthle cells.…”
Section: Afirma Gene Expression Classifiermentioning
confidence: 87%
“…In another single-center retrospective, unblinded study, Lastra et al [31] reported on the University of Pennsylvania experience, in which 132 cases of indeterminate cytology nodules were subject to GEC testing, including the categories of AUS/FLUS, FN, or FN with oncocytic features, with more than half of the cases being in the AUS/FLUS category (52%, 68/132). The prevalence of malignancy in the 50 cases in this study that had histopathological confirmation of diagnosis was 44% (22/50).…”
Section: Should a Microarray Gec Test Be Routinely Used On An Indetermentioning
confidence: 99%
“…In summary, based on the above studies that reported on sensitivity and specificity, GEC test sensitivity was reported to range from 83 to 100% and specificity from 7 to 52%, whereas the prevalence of malignancy in histopathologically confirmed study populations ranged from 17 to 51% [10, 29-31]. …”
Section: Should a Microarray Gec Test Be Routinely Used On An Indetermentioning
confidence: 99%
See 1 more Smart Citation